Diseño de una guía de procedimientos contables y tributarios para las empresas comercializadoras de productos de primera necesidad del cantón Saraguro - Cabrera Poma., Blanca Marlene (2022)
The curricular integration work called "DESIGN OF A GUIDE OF ACCOUNTING AND TAX PROCEDURES FOR COMMERCIALIZING COMPANIES OF FIRST NEED PRODUCTS OF THE SARAGURO CANTON" not required to keep accounts, was carried out with the purpose of providing the owners of the companies with an instrument of support and orientation, of how the accounting and tax processes should develop the activities in a logical, sequential and detailed manner, allowing them to obtain broader knowledge and carry out an adequate control and registration of their operations. To develop this degree work, some research methods were taken into account, such as inductive, analytical, scientific, deductive and synthetic, helping to obtain information from different sources such as books, web pages, scientific journals, etc. To carry out the situational diagnosis, the research technique was applied, such as the surveys that were carried out on the owners of the commercial companies of essential products with the objective of obtaining information on the level of knowledge that the owners have regarding accounting and tax matters, the procedures guide was designed according to their needs, establishing procedures, formats, examples and flow charts, facilitating compliance and adequate registration of their daily operations. The accounting and tax procedures designed were carried out so that they obtain detailed and orderly information where there are models and examples of documents, accounting record formats, standard entries according to the established processes in order to facilitate that the records of their operations are carried out correctly, allowing errors to be reduced and the resources obtained to be safeguarded, an instruction was also carried out on how to make the declarations step by step through the use of the web portal of the Internal Revenue Service for timely compliance with tax obligations. Finally, flowcharts of the accounting and tax procedures were designed with the purpose of graphically making known the steps that must be executed in a process and in a sequential manner, in order to guide the owners and workers who work in the companies, and with this, that they improve, manage, control and properly account the operations carried out, in order to reduce errors in their records, thus contributing to the continuous development of the processes for the companies that commercialize basic necessity products in the Saraguro Canton. 5 Once the objectives were fulfilled, it was concluded that this guide constitutes a valuable management tool for companies to facilitate compliance with procedures, improve efficiency in the activities carried out, and contribute to obtaining information in a clear, detailed and orderly manner related to accounting and tax.